2014
DOI: 10.18632/oncotarget.2168
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy balance modulates ovarian cancer progression and metastasis

Abstract: A high energy balance, or caloric excess, accounts as a tumor promoting factor, while a negative energy balance via caloric restriction, has been shown to delay cancer progression. The effect of energy balance on ovarian cancer progression was investigated in an isogeneic immunocompetent mouse model of epithelial ovarian cancer kept on a regimen of regular diet, high energy diet (HED) and calorie restricted diet (CRD), prior to inoculating the animals intraperitoneally with the mouse ovarian surface epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 85 publications
5
42
0
Order By: Relevance
“…Moreover, they showed increased levels of insulin, leptin, IGF-1, VEGF, and proinflammatory factors (IL-6). Instead, the mice group under CR showed a lower tumor burden as well as a great reduction in insulin, IGF-1, leptin, MCP-1, VEGF, and IL-6 levels (Al-Wahab et al 2014). Also, clinical trials demonstrated the effectiveness of the association chemotherapy/DR.…”
Section: Ovarian Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, they showed increased levels of insulin, leptin, IGF-1, VEGF, and proinflammatory factors (IL-6). Instead, the mice group under CR showed a lower tumor burden as well as a great reduction in insulin, IGF-1, leptin, MCP-1, VEGF, and IL-6 levels (Al-Wahab et al 2014). Also, clinical trials demonstrated the effectiveness of the association chemotherapy/DR.…”
Section: Ovarian Cancermentioning
confidence: 97%
“…Al-Wahab et al (2014) published a study showing the effects of energy balance in mouse models subjected to high energy diet or CR conditions. Mice group under high-energy diet showed the most extensive tumor formation accompanied by the highest tumor score at multiple sites.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Among gynecological tumors, ovarian cancer is one of the most common and the fifth cause of death in the female population (Reid et al 2017). Al-Wahab et al (2014) published a study showing the effects of energy balance in mouse models subjected to high energy diet or CR conditions. Mice group under high-energy diet showed the most extensive tumor formation accompanied by the highest tumor score at multiple sites.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…While hyperglycemia and obesity are thought to be contributing factors to cancer development and progression, caloric restriction has been associated with reduced cancer incidence [ 74 , 75 , 76 , 77 ]. During reduced calorie intake or exercise, the body switches to obtaining energy from fatty acid oxidation, which results in ketone bodies production.…”
Section: Mechanisms Regulating Chemokine Transcription In Ovarian mentioning
confidence: 99%